Are Sex and Gender Dimensions Accounted for in NICE and SIGN Psychiatry Guidelines? A Systematic Review - Rachel Hulme; Kate Womersley; Marina Politis; Alice Witt (BJPsych Open, 2025)
Aims: Sex and gender are critical determinants in the diagnosis, progression, and management of psychiatric conditions, influencing disease epidemiology, symptom presentation, treatment responses, and access to care. However, the extent to which these factors are systematically incorporated into UK psychiatric clinical guidelines has been unclear. To date, no review has assessed how sex and gender considerations are addressed in guidelines produced by the National Institute for Health and Care Excellence (NICE) or the Scottish Intercollegiate Guidelines Network (SIGN).